Cedrus deodara root rot disease-threat to the Himalayanforestry and environment - T. N. LAKHANPAL1, LAL SINGH and (Indian Phytopathology, 2002)
Studies on root rot disease of deodar (Cedrus deodara) caused by Phytophthora cinnamomi are reported for the first time from the Himalayan region. The disease resulted in widespread mortality of deodar trees near Chail, Shimla, Himachal Pradesh. About 200 trees are dead, and another 150-200 are at different stages of decay (chlorosis, defoliation, drying and shedding branches and bark). The disease has resulted in the decline and death of mature trees (>15" diameter); young regenerating plants arehealthy in spite of ample inoculum in the soil. Extensive ectomycorrhizal presence in such plants acts as the main deterrent to invasion by the pathogen. In older trees, where the ectomycorrhizal mantle is lost from short roots, the root surface is exposed to attack by the invading pathogen. The pathogen produces zoosporangia in the soil, each releasing 30-40 kidney shaped zoospores. This is the first report of any fungus causing such a large-scale disease of forest trees in the Indian Himalayas.